Activation-induced deaminase expression defines mature B cell lymphoma in the mouse - Gómez-Escolar, Carmen; Marina-Zárate, Ester; Ramiro, Almudena R. (Frontiers in immunology, 2023)
Germinal centers (GCs) are the sites of secondary antibody diversification and underlie the mechanism of action of many vaccination strategies. Activation-induced deaminase (AID) triggers secondary antibody diversification through the introduction of somatic changes in immunoglobulin genes which lead to the generation of antibodies of higher affinity and more specialized effector functions. However, AID can also target other genomic regions, giving rise to mutations and chromosome translocations with oncogenic potential. Many human lymphomas originate from mature B cells that have undergone the GC reaction, such as the diffuse large B cell lymphoma, the follicular lymphoma and Burkitt lymphoma, and carry chromosome translocations. Mature B cell lymphomagenesis has been modeled in the mouse by the genetic introduction of chromosome translocations. Here, we present an in-depth characterization of one such model, λ-MYC mice. We found that young pre-tumor stage mice had a prominent block in early B cell differentiation that resulted in the generation of very aggressive tumors lacking surface B cell receptor (BCR) expression, indicating that a large fraction of tumors in λ-MYC mice arise from B cell precursors rather than from mature B cells. Further, we assessed the contribution of AID to B cell lymphomagenesis in λ-MYC mice by using a genetic tracer of historical AID expression. Only a fraction of tumors contained cells of GC origin as defined by AID expression. AID-experienced tumors associated with longer survival and resembled mature B cell lymphomas. Thus, AID expression defines Burkitt lymphomagenesis in λ-MYC mice.